2022
DOI: 10.1186/s12964-022-00965-6
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in the molecular mechanisms of insulin resistance during a critical developmental window in Wistar rats

Abstract: Background Insulin resistance (IR) is a condition in which the response of organs to insulin is impaired. IR is an early marker of metabolic dysfunction. However, IR also appears in physiological contexts during critical developmental windows. The molecular mechanisms of physiological IR are largely unknown in both sexes. Sexual dimorphism in insulin sensitivity is observed since early stages of development. We propose that during periods of accelerated growth, such as around weaning, at postna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Research has highlighted sexual dimorphism in various metabolic parameters, particularly in glucose regulation. For instance, insulin signaling (IRS1), which is higher in males, and glucose-induced expression of GLUT4 in early stages affect glucose regulation differently between males and females [ 49 ]. This sexual dimorphism extends to metabolic impacts, with males showing increased insulin resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Research has highlighted sexual dimorphism in various metabolic parameters, particularly in glucose regulation. For instance, insulin signaling (IRS1), which is higher in males, and glucose-induced expression of GLUT4 in early stages affect glucose regulation differently between males and females [ 49 ]. This sexual dimorphism extends to metabolic impacts, with males showing increased insulin resistance.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the sexual dimorphisms observed in this study regarding glucose metabolism and IR corroborate with what has been demonstrated in different models of obesity and maternal obesity ( 71 ). Female sex hormones play a fundamental role in dimorphic insulin signaling since estrogens increase insulin sensitivity in metabolic tissues and upregulate insulin transcription in pancreatic beta cells as well as GLUT4 synthesis in adipose tissue and muscle ( 72 ). Female mice fed an HFD showed reduced susceptibility to developing obesity-induced IR and WAT inflammation when compared to HFD-fed males.…”
Section: Discussionmentioning
confidence: 99%
“…Before each experiment, adult rats were fasted for 12 h while P20 rats were fasted for 4 h. These fasting times were used because glucose reached basal levels and remained stable after this fasting period for each age [27]. Fasted animals were anesthetized with sodium Pentobarbital (40 mg/kg of weight) intraperitoneally; after the dissection, cervical dislocation was…”
Section: Primary Culture Of Pancreatic Islet Cellsmentioning
confidence: 99%
“…Therefore, NGF may promote beta-cell functional maturation. However, to our knowledge, no studies have assessed the NGF effects on GSIS in beta cells obtained from P20 rats, characterized by physiological insulin resistance due to high fasting plasma glucose and insulin levels [19,27].…”
Section: Introductionmentioning
confidence: 99%